Results and Performance of the World Bank Group 2014 : An Independent Evaluation - Independent Evaluation Group (World Bank, Washington, DC, 2021)
The year 2015 is pivotal in international development. As the era of the Millennium Development Goals (MDGs) concludes, work continues to take forward the unfinished MDG agenda and to define and meet the more ambitious Sustainable Development Goals (SDGs). In preparation for the new challenges, the World Bank Group is changing. A new strategy in 2013 set two ambitious goals: ending extreme poverty by 2030 and boosting shared prosperity for the bottom 40 percent in a sustainable manner. To achieve the twin goals and contribute significantly to the SDGs, it is important to reflect on the Bank Group’s experience with the MDGs to draw lessons for its engagement with the post-2015 agenda. This report also reviews the effectiveness of the Bank Group’s portfolio and country programs for delivering results, and its implementation of Independent Evaluation Group (IEG) recommendations.